Advances of Professional Education in Brazil and its historical subordination to the capitalist system (Research, Society and Development, 2019)
Historically, professional education in Brazil is based on policies aimed at the disadvantaged class. This is a reality that marks a persistent duality between basic education and professional education. Thus, the history of structural duality in Brazilian education is related to the history of the class struggle in capitalism. Given this reality, the objective of this study was to analyze historically the dilemmas of professional education in Brazil, contextualizing with the laws that govern this type of education in the country. In order to do this, it was referenced in some legal instruments on professional education in Brazil, and in studies of researchers such as Saviani, Frigotto, Machado e Kuenzer, because they are reference researchers in the thematic area of education and work. This research is qualitative, with an exploratory character, of the bibliographic and documentary type. The results indicate that the legal provisions related to professional education in Brazil are essentially related to the interests of capital; and despite the advances achieved in the last decade, with the creation of the Federal Network of Professional, Scientific and Technological Education, and of the Federal Institutes of Education, Science and Technology, it is necessary for Brazilian society to demand of its rulers measures vocational education fulfill its social mission of educating according to the sociopolitical, cultural, scientific and technological context.